PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA LABURUNCI KECAMATAN PASARWAJO KABUPATEN BUTON - Jufri Jufri; Nastia Nastia; Muh. Askal Basir (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze community participation in village development in Laburunci Village, Pasarwajo District, Buton Regency. The research employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation, involving purposively selected informants such as village officials, community leaders, and residents. The results indicate that community participation is uneven across development stages. Participation in the planning stage remains low due to limited information access and dominance of certain groups. In contrast, participation in the implementation stage is relatively strong, particularly through mutual cooperation supported by socio-cultural values. However, participation in the evaluation stage is still limited due to a lack of transparency and insufficient public involvement. These findings highlight the need to improve information transparency and strengthen inclusive community participation in village development